Using Industry Certifications to Improve the Marketability and Skill Development of Accounting and Finance Students - Joey Mehlhorn; Brittany Cole; Laura Hatch (International Journal of Business and Social Science Research, 2023)
This article focuses on optional business certifications that students can obtain while they are completing their undergraduate degree program. These certifications can benefit students in the job market and be helpful in supplementing real world business training in curriculum and address any skill gaps. Several business certifcaitons are represented with pertinent information on the process and benefits of certificate completion. The list of certificates is not meant to be exhaustive, but gives a starting point for business faculty looking to provide opportunities for student career development.